Molecular detection of HPV16 infections in cervical cancer samples of women patients from Dhi-Qar, Iraq - Jalil, Abduladheem (Journal of Biomedicine and Biochemistry, 2023)
Background and Objective The current study aims to detect the frequency of human papillomavirus (HPV16) 16 from cervical samples in Dhi Qar Governorate / Iraq based on molecular analysis.Method Between 2017 and 2020, this survey was conducted on 93 adult females who had cervical cancer and 60 healthy people as controls. Pa- tients’ ages ranged from 32 to 78. DNA was collected for molecular analy- sis and treated to PCR for minor capsid protein L2 gene amplification and identification.Results According to PCR data, HPV16 was present in 60 (65%) of the 93 cervical cancer cases, but only 5 (8%) of the healthy control group were HPV16 positive. The current survey found the highest rates of high-risk HPV16 infections in 2019 (78%) and 2020 (69%) compared to the lowest rates in 2017 (47%) of infections. Additionally, age groups have an impact on the rate of HPV16 infection; according to the most recent findings, the infection rate among elderly women declined while it increased among young women. On the other hand, the distribution of HPV16 infections according to the stages of cervical cancer revealed that stage IV (70%) had the greatest infection rates, followed by stage III (68%) and stage II (60%).Conclusion For accurate HPV16 detection, PCR is a reputable tech- nique. In addition, viral infections have surged recently, especially in young women, and are unmistakably linked to the advancement of cervical cancer. In the Thi-Qar province of Iraq, HPV16 infections are significantly linked to cervical carcinoma among women.